2001
DOI: 10.1002/dc.10002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fine‐needle aspiration in supraclavicular lymphadenopathy: A study of 106 patients and review of literature

Abstract: The simplicity and safety of the fine-needle aspiration (FNA) make it a useful procedure for the initial evaluation of supraclavicular lymphadenopathy. We analyzed data (106 patients) in combination with the data of three recently published studies (total 301 patients) to make the observations more meaningful. The usefulness of various ancillary techniques such as special histochemical stains (SHC), immunohistochemistry (IHC), and flow cytometry (FCM) in establishing specific diagnoses was also examined. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
38
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 12 publications
9
38
1
Order By: Relevance
“…There have, however, been studies reviewing biopsies of nodes in the 'supraclavicular' region, particularly regarding the diagnostic yield of FNAC. Such studies have found malignancy rates of between 55 and 71 %, with a higher lymphoma:metastatic carcinoma ratio in subjects younger than 40 when compared to those above 40 years [6][7][8][9][10]. In one of these studies, the actual malignancy rate was found to be as high as 86.5 % (n = 45) on final histology of excisional biopsy [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have, however, been studies reviewing biopsies of nodes in the 'supraclavicular' region, particularly regarding the diagnostic yield of FNAC. Such studies have found malignancy rates of between 55 and 71 %, with a higher lymphoma:metastatic carcinoma ratio in subjects younger than 40 when compared to those above 40 years [6][7][8][9][10]. In one of these studies, the actual malignancy rate was found to be as high as 86.5 % (n = 45) on final histology of excisional biopsy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although FNAC is a well-established first diagnostic tool for the evaluation of lymph nodes [3], only core biopsy or excision biopsy will be sufficient for the formal diagnosis of lymphoma when further analytical techniques are unavailable, such as immunohistochemistry, flow cytometry and specific stains [9,[14][15][16]. The British Society of Pathologists recommend whole node specimens where possible due to the volume of tissue required for testing to secure a diagnosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Left sided supraclavicular lymph node (Virchow's) has represented the final common pathway of the infradiaphragmatic sites (8). As a result; infradiaphragmatic tumors from abdominopelvic region has mostly metastasized to left supraclavicular fossa whereas supradiaphragmatic tumors from thoracic cavity could metastasize to both right and left region (9). Left supraclavicular lymph nodes might be involved in gastric carcinoma metastasis (Virchow's node) (3).…”
Section: Discussionmentioning
confidence: 99%
“…The cytological criteria for the diagnosis of possible tubercular lymphadenitis is epithelioid cell granulomas with or without multinucleated giant cells and presence or absence of caseating necrosis [4].It should be kept in mind that lymphadenopathy is the most common presentation of extra pulmonary tuberculosis [6,7]. Pediatric cervical lymphadenopathy is a challenging medical condition for the patient, the parent, and the physician.…”
Section: Discussion:-mentioning
confidence: 99%
“…However biopsy still remains important in accurate and definite diagnosis of a tumor [6]. Cytoimmunochemistry is opening up newer doors for diagnostic cytopathology specially in the field of oncology [7]. Some authors state that cytology is a more readily accepted methodology for the evaluation of deep seated lymph nodes where surgical resection is not possible.…”
mentioning
confidence: 99%